POSSIBLE ABUSES OF ARTIFICIAL INTELLIGENCE IN THE STUDY PROCESS - Srečo Zakrajšek (Innovative Issues and Approaches in Social Sciences)
As part of the project Use of Artificial Intelligence (ChatGPT) in the Course, Leadership and Organisation of Media Production at FUDŠ, we conducted a study to identify potential abuses of artificial intelligence in the study process.The findings indicate that students are aware of potential abuses of AI in the study process and propose specific measures to limit or prevent such behaviour, as it could negatively affect the academic process and create disparities among students. Students believe that those who abuse AI are primarily motivated by a lack of time, low levels of knowledge, or limited motivation.The main forms of abuse include creating content that students present as their own, generating assignments without understanding the material, and cheating during exams.